Uma história ambiental do rio Passo Fundo: 1934-2007 - Lima, Caroline Lisboa dos Santos de (2018)
Environmental public policies are relatively recent in Brazil. It was from the 1970s that the environment began to gain greater importance in the national political agenda. However, this does not mean that public authorities have not had initiatives that have impacted the environment, even in periods when their conservation was not on the agenda. The actions of sanitation, the disposal of various types of waste, the cleaning and distribution of urban occupation were, for example, functions that the municipal administrations had to fulfill, which ended up impacting not only the local environment but also the society with him. The Passo Fundo river was used as a reference since the first populations settled there, the river gave its name to the place and more than that, it ended up marking the daily life of the population that lived and lives in its vicinity. Therefore, the human relationship with the Passo Fundo river between the years of 1934 and 2007 is the subject of this dissertation. The paper includes notes on human uses, initiatives and public policies in relation to the Passo Fundo river, seeking to analyze, among other issues, the role of ecological movements and the press in the consolidation of an environmental policy in the municipality. The present understandings are theoretically based on Environmental History, which seeks to understand the most diverse aspects, interests and results of human interaction with the natural environment. Among the authors used as reference are Donald Worster, José Augusto Pádua and Gilmar Arruda. Federal, state and municipal legislation, journalistic publications and civil surveys on the subject were used as documentary apparatus. Finally, the problem of this investigation is to demonstrate how the initiatives, public policies and social actions interfered in the historical existence of the river Passo Fundo, identifying who were the subjects and what interests implied in that process.